Prevalence of T-2 Toxin in the Food and Beverages of Residents Living in a Kashin–Beck-Disease Area of Qamdo, Tibet - Jiang, Tong; Yan, Junan; Tan, Hongxing; Pu, Zhu; Wang, Ou; Liu, Tao; Chen, Zhaoyu; Gao, Jiaxiang; Wang, Jun; Lin, Jianhao; Huo, Junsheng; Huang, Jian (Nutrients, 2024)
It has been strongly suggested that selenium deficiency and T-2 toxin contamination have a strong relationship with the occurrence and development of Kashin–Beck disease (KBD). In order to provide information for understanding the high prevalence of KBD in Tibet, this study collected the responses to a cubital venous blood and dietary questionnaire of 125 subjects including 75 KBD patients and 50 healthy controls in a KBD-prevalent county (Luolong County) in Tibet, China. A total of 10 household local families were randomly selected in this area, and local diet samples of brick tea, Zanba powder, milk residue, and hulless Barley were collected from these residents. Selenium content in blood was detected by inductively coupled plasma mass spectrometry (ICP-MS). The T-2 toxin contamination level in food sample was assayed using an ELISA kit. The selenium levels of patients and controls were 42.0 ± 19.8 and 56.06 ± 22.4 μg/L, respectively. The serum selenium level in controls was higher than that in patients, but there was no significant difference, and the serum selenium level both in patients and controls in Tibet was lower than the normal range. The results of the dietary survey showed that the number of respondents who consumed butter tea was large; 46.67% of patients indicated that they drank buttered tea every day, which was significantly higher than in controls. The contents of T-2 toxin in Zanba powder, milk residue, hulless barley and drinking water samples were below the detection limit (0.05 μg/kg); this result was labeled Tr. Unexpectedly, the contents of T-2 toxin in brick tea were higher, with average levels of 424 ± 56 μg/kg in Detong village and 396 ± 24 μg/kg in Langcuo village. For the first time, we report the presence of an extremely high concentration of T-2 toxin in brick tea of Tibet.